Ecosystem respiration - Robroek, Bjorn J. M.; Jassey, Vincent E. J.; Kox, Martine A. R.; Berendsen, Roeland L.; Mills, Robert T. E.; Cécillon, Lauric; Puissant, Jéremy; Meima–Franke, Marion; Bakker, Peter A. H. M.; Bodelier, Paul L. E. (Dryad Digital Repository, 2015)
To asses the effect of vascular plant removal in aforementioned experiment, one year after the start of the experiment, we measured carbon dioxide respiration rates on 10 cm diameter collars using an automated soil CO2 flux system (LI-8100, LI-COR Biosciences, USA). We compare the fluxes from the vascular plant removal plots with respiration rates from comparable areas in the control plots with little or no vascular plant cover, and assessed the relationship with the amount of removed biomass.